External validation of the paediatric risk of malignancy index. (5th January 2015) - Hermans, AJ; Kluivers, KB; Massuger, LF; Coppus, SF
Abstract : Objective: This study aimed to validate the paediatric risk of malignancy index (PRMI), as previously published. Design: External validation study. Setting: Academic hospital: Radboud University Medical Center. Population: Female paediatric patients under the age of 18 years diagnosed with, or treated for, an adnexal mass between January 1999 and October 2013. Methods: Information was collected on diagnosis, presenting symptoms, and signs and imaging characteristics. The PRMI was calculated for each patient. Sensitivity, specificity, and positive and negative predictive values were calculated, and the results were visualised using a receiver operating characteristic curve (ROC curve). Main outcome measures: Histological diagnosis, discriminative performance using the area under the curve (AUC) of the ROC curve and sensitivity and specificity. Results: Seventy‐eight patients were included, with a median age of 12 years. A malignant mass was found in 17 patients (21.8%). The PRMI with a cut‐off value of 7 resulted in a sensitivity of 70.1% (95% CI 44.1–89.6%) and a specificity of 85.3% (95% CI 73.8–93.0%). The area under the ROC curve was 0.868 (95% CI 0.756–0.980). Conclusions: The PRMI showed less discriminative capacity than originally published, but its performance was still good; however, further prospective validation studies are needed to define whether the model is useful in daily clinical practice.